Detection of Toxigenic Clostridium difficile in Stool Samples by Real-Time Polymerase Chain Reaction for the Diagnosis of C. difficile-Associated Diarrhea - Peterson, Lance R.; Manson, Rebecca U.; Paule, Suzanne M.; Hacek, Donna M.; Robicsek, Ari; Thomson, Richard B; Kaul, Karen L. (Clinical infectious diseases, 2007)
Background. Clostridium difficile-associated diarrhea (CDAD) is the major cause of health care-associated infectious diarrhea. Current laboratory testing lacks a single assay that is sensitive, specific, and rapid. The purpose of this work was to design and validate a sensitive and specific real-time polymerase chain reaction (PCR) diagnostic test for CDAD. Methods. This observational validation study of a new real-time PCR assay occurred from July 2004 through April 2006 and involved the testing of 1368 stool samples. As the final validation portion of the investigation, 350 inpatients were prospectively interviewed for clinical findings for 365 episodes of diarrheal illness. Test results and clinical criteria were used to assess the performance of 4 assays. Results. Using clinical criteria requiring at least 3 loose stools in 1 day as part of the reference standard for a positive test result supporting CDAD, the sensitivity, specificity, and positive and negative predictive values were 73.3%, 97.6%, 73.3%, and 97.6%, respectively, for enzyme immunoassay; 93.3%, 97.4%, 75.7%, and 99.4%, respectively, for real-time PCR; 76.7%, 97.1%, 69.7%, and 97.9%, respectively, for cell culture cytotoxin assay; and 100.0%, 95.9%, 68.2%, and 100.0%, respectively, for anaerobic culture (for toxigenic C. difficile strains). The real-time PCR and anaerobic culture assays were significantly more sensitive than the enzyme immunoassay (P < .01 to P < .05). Conclusions. With an assay turnaround time of <4 h, real-time PCR is a more sensitive and equally rapid test, compared with enzyme immunoassay, and is a feasible laboratory option to replace enzyme immunoassay for toxigenic C. difficile detection in clinical practice, as well as for use during the development of new therapeutic agents.